2015
DOI: 10.1039/c4dt02392g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxicity, DNA interaction and cell cycle studies of trans-diiodophosphine Pt(ii) complexes

Abstract: a Platinum complexes, bearing aliphatic amines and phosphine ligands in trans configuration with iodide as leaving groups, are synthesized and characterized. The crystal structure of trans-PtI 2 (isopropylamine)-(PPh 3 ) is reported. The complex bearing isopropylamine is demonstrated to be the best candidate as its cytotoxic activity is comparable to or better than cisplatin. A remarkably higher interaction of the complexes with DNA is reported as compared to the parent chlorido series. Cell cycle studies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…15 Moreover, for some trans-diiodophosphine Pt(II) complexes the interaction with DNA was demonstrated and a correlation of such ability with cytotoxicity was also supposed. 16 In this connection, the capacity of the most active complex 2a to coordinate DNA was investigated by ICP-AES technique, in comparison with cisplatin ( Fig. 2).…”
Section: Binding To Dnamentioning
confidence: 99%
“…15 Moreover, for some trans-diiodophosphine Pt(II) complexes the interaction with DNA was demonstrated and a correlation of such ability with cytotoxicity was also supposed. 16 In this connection, the capacity of the most active complex 2a to coordinate DNA was investigated by ICP-AES technique, in comparison with cisplatin ( Fig. 2).…”
Section: Binding To Dnamentioning
confidence: 99%
“…It has previously been shown that the action of nonconventional platinum drugs with aliphatic amines in the trans configuration can be modulated by replacing one of the trans aliphatic amines. As examples, a steroid-functionalized amine increases the selectivity of the complex, , phosphines modulate drug uptake, , and functionalizing the ligand with a DNA intercalator affords a dual-action platinum complex. , In the present study, we developed an alternative synthetic methodology that affords perfluorinated chain-modified platinum­(II) complexes by directly coupling the perfluorinated chain to a 3-(pyridin-3-yl)­propanoic acid already coordinated to a Pt­(II) center, which to the best of our knowledge is the first time such an approach has been reported for platinum­(II) complexes. Perfluorinated chains are known to endow compounds with thermoresponsive properties, , and related complexes with long hydrocarbon chains were also prepared for comparison purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The latest reviews and the large number of contributions therein identify new complex designs to face the known side effect problems of these antitumor drugs [1]. One of the latest contributions to this field has been the results that we published when studying the impact of the leaving group in the reactivity and cytotoxicity of the iodido complexes [2,3]. Looking for a new design, our group of researchers reevaluated cis platinum iodido complexes; their reactivity turned out to be quite unexpected versus sulfur donor biomolecules [4].…”
Section: Introductionmentioning
confidence: 99%